Application of Clavien–Dindo classfication-grade in evaluating overall efficacy of laparoscopic pancreaticoduodenectomy - Song, Xiangyang; Ma, Yu; Shi, Hongyun; Liu, Yahui (Frontiers in Surgery, 2023)
Abstract Background：The Clavien-Dindo classification（CDC） has been widely accepted and applied in clinical practice. We investigated its effectiveness in prediction of major complications（LPPC）after laparoscopic pancreaticoduodenectomy（LPD）and associated risk factors. Methods：A retrospective analysis was conducted of clinical data of 793 patients undergoing LPD from April 2015 to November 2021 were. CDC was utilized to grade postoperative complications and analyze the differences. Risk factors of LPPC were identified according to univariate and multivariate analyses. Resluts:For the 793 patients undergoing laparoscopic pancreaticoduodenectomy in the northeast of China, 260 (32.8%) patients reported LPPC, pancreatic fistula in 169（21.3%） patients, biliary fistula in 44（5.5%） patients, delayed gastric emptying in 17（2.1%） patients, post pancreatectomy hemorrhage in 55（6.9%） patients, intestinal fistula in 7（0.8%） patients, abdominal infections in 59 （7.4%） patients and pulmonary complication in 28（3.5%） patients. All complications were classified into five levels with the C-D classification(Grade IV),with 83(31.9%) patients as grade I, 91 (35.0%) as grade II, 38 (14.6%) as grade IIIa, 24 (9.2%) as gradeIIIb,9 (3.5%) as grade IV and 15 (5.8%) as grade V. 86(10.8%) patients experienced major complications (grade III- V).The results of univariate and multivariate analysis revealed the independent risk factors for laparoscopic pancreaticoduodenectomy complications to be preoperative total bilirubin (P=0.029, OR=1.523), soft pancreas texture (P<0.001, OR=1.399), male (P=0.038, OR=1.396) and intraoperative transfusion (P=0.033, OR=1.517). Preoperative total bilirubin (P=0.036, OR=1.906) and intraoperative transfusions (P=0.004, OR=2.123) were independently associated with major postoperative complications. The influence of different bilirubin levels on C-D grade of complications was statistically significant (P=0.036, OR=1.906). Conclusions：The Clavien-Dindo classification (CDC) may serve as a valid tool to predict major postoperative complications and contribute to perioperative management and comparison of surgical techniques in different medical centers.